Towards an ideotype for food-fuel dual-purpose wheat in Argentina with focus on biogas production - Gabbanelli, Nadia; Erbetta, Elisa; Sanz Smachetti, María Eugenia; Lorenzo, Maximo; Talia, Paola Mónica; Ramirez, Ignacio; Vera, Magdalena; Durruty, Ignacio; Pontaroli, Ana Clara; Echarte, María Mercedes (BioMed Central, 2021)
Wheat straw, one of the most abundant agricultural residues worldwide, can be used to produce biogas, which is considered one of the most efficiently produced renewable energies. Wheat grown with the dual-purpose of producing food and biogas should display simultaneously high grain and straw yields, low lodging susceptibility and high conversion efficiency of straw into biogas. The aims of this study were to determine the best food-fuel dual-purpose wheat candidates among 36 wheat genotypes—including French, CIMMYT and local (Criollo) germplasm—used in breeding programs in Argentina and to gain some insights into the relationships between key traits relevant for dual-purpose wheat genotypes.